Productive and reproductive performance from buffalo herds of Cuba and Brazil. Their utility to breeding work in Cuba - Fraga, L. M.; de Amorim, A. [UNESP]; Mendes, A. [UNESP]; Stéfano, F. [UNESP]; Méndez, M.; García, Y.; Guzmán, G.; Mora, M. (My University, 2010)
It was conducted a comparative study of bubaline populations of Cuba and Brazil with 7346 y 10152 records respectivaly of milking and reproductive traits corresponding to calving period between years 1962 - 2001 with 14 herds (Brazil) and 1985 - 2008 with 62 herds (Cuba). The possibilities of mixed and random regression models are stressed in prediction of genetic values and repetabilities and also possible joint works between both countries in this sence. It was outlined 13 general conclusions related with differences in milking production and reproductive performance of cow buffa loes of both countries that can be used as guides in future projections of breeding work. The use of mixed and random regression models processing s imilar databases without genealogy as the used in the present study are common in Cuba and possibly in other countries to handle the initial situation accounted for amelioration of buffaloes for milking and reproduction.
Keywords: Dairy reproduction performance models breeding